De spookachtige vrede 1938-1939 : twee jaren Europese politiek die leiden tot de tweede wereldoorlog - Mosley, Leonard (Amsterdam : H.J. Paris, 1970)
A book describing European politics during the years 1938 and 1939 and tries to outline the events that led to world war II.
Vvu collection